Crop Diversification Grown as Strip Intercropping Can Improve Farmers' Return in a Dryland with Sandy Soil - I Komang Damar Jaya; Herman Suheri; Wayan Wangiyana; Akhmad Zubaidi (Postgraduate, University of Mataram, 2024)
Maize and mungbean are two common crops grown in dryland areas with sandy soil structures. This study aimed to explore the potential of adding cayenne pepper to increase crop diversity using strip intercropping (SI) as a potential system to improve farmers' return. There were seven treatments tested: monoculture maize, monoculture mungbean, monoculture cayenne pepper, SI maize and mungbean, SI maize and cayenne pepper, SI mungbean and cayenne pepper, and SI maize, mungbean, and cayenne pepper. The size of the treatment plot was 700 cm × 500 cm, and all the treatments were arranged in a Randomized Block Design with three replications. The study showed no difference in the land equivalent ratio (LER) for all the SI treatments, with a value of around 1.0. This indicates no advantage of SI over monocropping in terms of land usage. However, when the market prices valued the yield of each component crop in SI at harvest, the highest economic value came from monocrop cayenne pepper treatment (IDR 246 million ha-1). All the SI treatments involving cayenne pepper resulted in a higher return than the monoculture of maize or mungbean. The lowest economic value was shown by monoculture mungbean treatment (IDR 33.1 million ha-1). These results indicate that diversifying crops can improve farmers' return, especially by incorporating cayenne pepper in dryland with sandy soil.